PENYULUHAN TENTANG SADARI (PEMERIKSAAN PAYUDARA SENDIRI) UNTUK MENDETEKSI DINI KANKER PAYUDARA DI DUKUH PEDES ARGOMULYO SEDAYU BANTUL - Widarti, Sri (Jurnal Pengabdian Kepada Masyarakat Mulia Madani Yogyakarta, 2025)
Background: Breast cancer is a cancer with a fairly high mortality rate and is a type of malignant disease that often attacks women. The prevalence and mortality of cancer reached at least 19.3 million cases in 2020.Objective: Community service activities are to increase the knowledge of BSE (Breast Self-Examination) mothers and increase the level of health and monitoring of the incidence of breast cancer in women.Method: Providing counseling using presentation methods using PPT, video screenings and demonstrations about BSE movements.Results: The preparation stage showed that all participants had never received education about BSE before, in fact 95% of the 30 participants were hearing about BSE for the first time. Low initial knowledge can be seen from the results of direct interviews conducted where the majority of mothers' knowledge level is still low about BSE and breast cancer. After education and training there was an increase in mothers' knowledge about BSE. It is recommended that health workers periodically provide education about BSE to women, especially mothers. Keywords: REALIZE, Counseling